Identifikasi Varietas Contoh untuk Karakter Penciri Spesifik sebagai Penunjang Harmonisasi Pengujian BUSS Padi - Sitaresmi, Trias; Yunani, N.; Zakki, K. A.F.; Mulsanti, Indria W.; Utomo, Sudibyo T.W.; Daradjat, A. A. (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2013)
DUS testing (distinctness, uniformity, stability) for a new variety is required for plant variety protection, using international standard method stated on the test guideline. Identification of specific traits needs to be done, in order to obtain stable characters that are valid to be used as standard variety to represent appearance of class-specific characters. This study aims to 1) evaluate specific/asteric characters (*) according to UPOV descriptors; 2) Identify genotypes that can be used as standard varieties for the appearance of specific characters in the process of harmonization of DUS testing among rice producing countries in Southeast Asia. Activities included characterization of 56 genotypes of irrigated and upland rice and were carried out at the Experimental Station of Indonesian Center for Rice Research in Sukamandi, West Java, from September 2011 to January 2012. Observation of plant characters was based on PPU. The result showed that from 43 of class expression of asteric qualitative characters (*), only 28 class expressions were identified in the materials. The characters class expressions are represented by 25 genotypes/varieties. Another eleven more characters asteric (character essential for the harmonization of test results for the PVP), which were not represented by the candidate sample varieties in this study need to identified.